Virtual tour in the Sunken "villa ingresso a protiro" within the underwater archaeological park of baiae - Barbieri, Loris; Peluso, Raffaele; Bruno, Fabio; Davidde Petriaggi, Barbara; Cozza, Marco; Rizvic, Selma; Skarlatos, Dimitrios; Cozza, Alessandro; Petriaggi, Roberto; Lagudi, Antonio (My University, 2019)
The paper presents the application of some Virtual Reality technologies developed in the Horizon 2020 i-MARECulture project to the case study of the sunken "Villa con ingresso a protiro", dated around the II century AD, and located in the Marine Protected Area - Underwater Park of Baiae (Naples).The i-MARECulture project (www.imareculture.eu), in fact, aims to improve the public awareness about the underwater cultural heritage by developing new tool and techniques that take advantage of the virtual reality technologies to allow the general public to explore the archaeological remains outside of the submerged environment.To this end, the paper details the techniques and methods adopted for the development of an immersive virtual tour that allow users to explore, through a storytelling experience, a virtual replica and a 3D hypothetical reconstruction of the complex of the "Villa con ingresso a protiro".
Keywords: 3D hypothetical reconstruction; Digital storytelling; Virtual Diving; Virtual Heritage; Virtual Reality